Strategies for Integrating Problem-Based Learning, Teaching Modules, and Formative Assessments to Enhance Learning Outcomes and Critical Thinking Skills - Siti Nuraini Ajid; Dian Artha Kusumaningtyas; Koesoemo Ratih; Shairmane Lava (Universitas Muhammadiyah Surakarta, 2025)
In an ideal educational setting, students actively engage with content, apply critical thinking to solve real-world problems, and consistently demonstrate improved learning outcomes. However, many educational environments lack integrated strategies that connect theoretical knowledge with practical applications, leading to passive learning and underdeveloped critical thinking skills. This study addresses these gaps by developing and implementing a novel framework—Problem-Based Learning, Teaching Modules, and Formative Assessments (PLTMFA)—designed to enhance learning outcomes and critical thinking skills, particularly in the context of Magnitudes, Units, and Measurements. Grounded in instructional design principles, the PLTMFA approach emphasizes active learning and continuous, meaningful assessments to ensure student engagement and cognitive development. Given the increasing demand for critical thinking and problem-solving skills, there is an urgent need to explore and validate such innovative teaching methods. The study’s primary objectives are to develop the PLTMFA framework, apply it in a classroom setting, and evaluate its effectiveness. Data collected through comprehension tests, questionnaires, and observations were analyzed to assess the impact on student performance. Findings indicate that PLTMFA significantly improves both learning outcomes and critical thinking skills, demonstrating its potential as an effective solution to current educational challenges.